Spray Deposition and Drift as Influenced by Wind Speed and Spray Nozzles from a Remotely Piloted Aerial Application System - Daniel E. Martin; Jeffrey W. Perine; Shanique Grant; Farah Abi-Akar; Jerri Lynn Henry; Mohamed A. Latheef (Drones)
The phenomenal growth of remotely piloted aerial application systems (RPAASs) in recent years has raised questions about their impact on the off-target movement of plant protection products. The spray droplet spectrum is one of the important determining factors that govern droplet trajectories and off-target movement of pesticide particles. A field study was conducted to compare in-swath and downwind spray deposition on ground samplers from a 20 L RPAAS platform, equipped with three different nozzles, which provided fine, medium, and extra-coarse droplet spectra. A fluorescent dye was used as a tracer to determine spray deposition. Airborne spray droplets were measured at 10 and 20 m downwind. Downwind deposition measured on ground samplers showed that the extra-coarse nozzle received significantly fewer deposits than the medium or the fine nozzle. Similarly, the airborne deposition for the extra-coarse nozzle was significantly less compared to either the fine or the medium nozzle. Linear mixed effects modeling confirmed these results and showed that wind speed served as a covariate by refining the deposition differences among nozzles. Results indicated that spray drift from RPAAS platforms may be mitigated by using appropriate nozzles that produce larger droplet spectra. These results will provide aerial applicators with a better understanding of the best management practices to mitigate drift.